(untitled) - Mundy, Liza (New York, 2017)
Their efforts shortened the war, saved countless lives, and gave them access to careers previously denied to them. A strict vow of secrecy nearly erased their efforts from history; now, through dazzling research and interviews with surviving code girls, bestselling author Liza Mundy brings to life this riveting and vital story of American courage, service, and scientific accomplishment.
Keywords: Chiến tranh thế giới, 1939 - 1945,World War, 1939-1945